Pastoral care to people living with HIV/Aids: A pastoral response that is contextual and liberating - Buffel, O. (Practical Theology in South Africa = Praktiese Teologie in Suid-Afrika, 2006)
The main argument of this article is that the response of the church in general, and that of pastoral care in particular has not been appropriate, contextual or liberating. This inappropriate response could have contributed to the extreme suffering of people living with HIV / AIDS. The article traces some of the inappropriate responses of the church and pastoral care in particular. For pastoral care to be contextual and liberating, it has to undergo a paradigm shift. Furthermore it is argued that pastoral care needs to reclaim an understanding of the true nature of the church as the body of Christ. Pastoral care needs also to learn from the methodology of liberation theology, that takes the situation and context of the people seriously.
Paid